Physiology of Glyphosate-Resistant and Glyphosate-Susceptible Palmer Amaranth (Amaranthus palmeri) Biotypes Collected from North Carolina - Jared R. Whitaker; James D. Burton; Alan C. York; David L. Jordan; Aman Chandi (International Journal of Agronomy)
Glyphosate-resistant (GR) biotypes of Palmer amaranth are now commonly found across the southern United States. Experiments were conducted to characterize physiological differences between a GR biotype and a glyphosate-susceptible (GS) biotype from North Carolina. The GR biotype had an 18-fold level of resistance based upon rates necessary to reduce shoot fresh weight 50%. Shikimate accumulated in both biotypes following glyphosate application, but greater concentrations were found in GS plants. Absorption and translocation of 14C-glyphosate were studied in both biotypes with and without an overspray with commercial glyphosate potassium salt (840 g ae ha−1) immediately prior to 14C-glyphosate application. Greater absorption was noted 6 h after treatment (HAT) in GS compared with GR plants, but no differences were observed at 12 to 72 HAT. Oversprayed plants absorbed 33 and 61% more 14C by 48 and 72 HAT, respectively, than plants not oversprayed. 14C distribution (above treated leaf, below treated leaf, roots) was similar in both biotypes. Together, these results suggest that resistance in this biotype is not due to an altered target enzyme or translocation but may be in part due to the rate of glyphosate absorption. These results also are consistent with resistance being due to increased gene copy number for the target enzyme.